A Non-Destructive Testing Based on Electromagnetic Measurements and Neural Networks for the Inspection of Concrete Structures - Al Cantara Jr, Naasson P. de [UNESP]; Costa, Danilo C. [UNESP]; Guedes, Diego S. [UNESP]; Sartori, Ricardo [UNESP]; Bastos, Paulo S. S. [UNESP] (Trans Tech Publications Ltd, 2011)
This paper presents a new non-destructive testing (NDT) for reinforced concrete structures, in order to identify the components of their reinforcement. A time varying electromagnetic field is generated close to the structure by electromagnetic devices specially designed for this purpose. The presence of ferromagnetic materials (the steel bars of the reinforcement) immersed in the concrete disturbs the magnetic field at the surface of the structure. These field alterations are detected by sensors coils placed on the concrete surface. Variations in position and cross section (the size) of steel bars immersed in concrete originate slightly different values for the induced voltages at the coils.. The values for the induced voltages were obtained in laboratory tests, and multi-layer perceptron artificial neural networks with Levemberg-Marquardt training algorithm were used to identify the location and size of the bar. Preliminary results can be considered very good.
Keywords: Non-Destructive Testing; Eddy Current Testing; Concrete Structures; Concrete Re nforcement; Artificial Neural Networks